2016
DOI: 10.24252/lp.2016v19n1a10
|View full text |Cite
|
Sign up to set email alerts
|

Profesionalisme Guru Dalam Peningkatan Mutu Pendidikan

Abstract: Abstrak:Tujuan penelitian adalah untuk mengetahui profesionalisme guru dalam peningkatan mutu pendidikan di SDN 65 Katteong Kabupaten Pinrang. Penelitian ini adalah penelitian kualitatif dan instrumen penelitian yang digunakan adalah observasi, wawancara, dan dokumentasi. Adapun teknik analisis datanya adalah teknik analisis deskriptif (non statistik). Hasil penelitian: Pertama, profesionailsme guru dalam peningkatan mutu pendidikan di SDN 65 Katteong Kab. Pinrang dapat dilihat dari 4 (empat) aspek kompetensi,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
26

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 1 publication
0
16
0
26
Order By: Relevance
“…Seorang guru yang menjiwai terhadap profesinya sebagai pendidik 20 , maka memahami profesionalitas dalam suatu pekerjaan khususnya dalam dunia pendidikan. Dimana seorang pendidik pasti akan mengutamakan mutu dan kualitas pendidikan sesuai tututan dan kebutuhan masyarakan, agar dapat menciptakan sumber daya manusia yang berkualitas di masa depan, dan siap menghadapi tantangan kehidupan, serta persaingan dalam hidup bermasyarakat.…”
Section: B Kajian Teoriunclassified
“…Seorang guru yang menjiwai terhadap profesinya sebagai pendidik 20 , maka memahami profesionalitas dalam suatu pekerjaan khususnya dalam dunia pendidikan. Dimana seorang pendidik pasti akan mengutamakan mutu dan kualitas pendidikan sesuai tututan dan kebutuhan masyarakan, agar dapat menciptakan sumber daya manusia yang berkualitas di masa depan, dan siap menghadapi tantangan kehidupan, serta persaingan dalam hidup bermasyarakat.…”
Section: B Kajian Teoriunclassified
“…Pedagogic competence. According to Yunus (2016), academic skill, namely the ability to manage learning which includes the understanding of students, designing, and implementing education and development of students to actualize the various potentials possessed.…”
Section: The Distribution Of Questionnaires To 68 Prospective Teachermentioning
confidence: 99%
“…So quality education can produce professional-minded teachers. Similar to Yunus (2016), quality education is education that can produce graduates who have competencies, both professional (academic) and vocational (pedagogic) competences, which are based on personality and social competences.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that school principals in Qingdao, China have typical instructional leadership that affects teacher professional learning, the importance of self-efficacy in shaping teacher teaching practices (Liu & Hallinger, 2018). Yunus (2016) explained that the professionalism of teachers at SDN 65 Katteong can be seen from 4 competency aspects; professional, pedagogic, personal, and social. Efforts can be made to improve teacher quality by involving scientific meetings, continuing studies informal institutions, participating in professional organizations, and participating in science competitions.…”
Section: Introductionmentioning
confidence: 99%